Climate, socioeconomic factors and spatial distribution of some worldwide arboviruses: a review of the literature - Parra, Gabriela Elisa; Ribeiro, Ana Cristina; Uehara, Sílvia Carla da Silva André (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
The spread of arboviruses can be influenced by factors such as climate, socioeconomic and spatial distribution. The identification of populations at highest risk of exposure to arboviruses is an important topic in the public health scenario. Therefore, the present study is a review of the literature, which aimed to identify the association between the spatial distribution of Dengue Virus, Zika Virus and Chikungunya Virus and the social, environmental and economic aspects of individuals affected by arboviruses, the based on the analysis of published literature on the topic. Articles published in Portuguese, Spanish and English between 1997 and 2019 were included; and studies that addressed the clinic, infection, molecular biology, genetics, entomology and microbiology of viruses and mathematical modeling studies and reviews were excluded. The search for articles was carried out in the IBECS databases; CINAHL; MEDLINE; PubMed; Web of Science. After data mapping, PRISMA was used to extract the data. Therefore, of the 32 articles included in the analysis, the results showed that climatic factors such as temperature and precipitation affect the origin, evolution and distribution of vectors; and, consequently, the transmission of related pathogens. Furthermore, when considering socioeconomic aspects, populations from regions with greater social vulnerability are at greater risk of becoming ill from an arbovirus. Therefore, these results suggest that climatic factors and socioeconomic aspects are associated with the spatial distribution of arboviruses, making it essential to develop efficient control and prevention measures for arboviruses, especially in the most vulnerable regions.